ANALISIS TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN PENDAFTARAN RAWAT JALAN DI RUMAH SAKIT PKU MUHAMMADIYAH WONOGIRI - Nila Erlinawati; Sri Suparti; Wahyu Wijaya Widiyanto (Journal Health Information Management Indonesian, 2025)
Patient satisfaction is an important part of health facilities. The level of patient satisfaction depends on the quality of service. The waiting time for patients shows < 10 minutes, there is only one registration counter and there is no division between counters for general patients and patients using BPJS cards. The purpose of this study was to analyze the level of satisfaction with outpatient registration services at PKU Muhammadiyah Wonogiri Hospital. The type of research used is quantitative research with analytic descriptive research methods with a cross sectional design. Data collection techniques using outpatient questionnaires. Univariate, bivariate and multivariate analyzes with the chi square test were used in this study. The sample of this study consisted of 100 outpatients as many as 100 people. The results of the statistical test analysis using the Chi-square test showed that there was a significant relationship (p-value <0.05) for the Responsiveness variable p = 0.015, Reliability p-value = 0.015, Assurance p- value = 0.039, empathy p = 0.003, physical evidence (tangibles) p-value = 0.000. Based on the results of multivariate analysis, it was found that the elements most strongly related to patient satisfaction with outpatient registration services were empathy, OR 7.144 (95% CI: 1.005 – 50.748) and tangibles, OR 10.487 (95% CI: 1.777). – 61,898).